The State of Solar Wind Heavy Ions in Interplanetary Coronal Mass Ejection–Driven Geomagnetic Storms - Cong Wang; Fei He; Xiaoxin Zhang (The Astrophysical Journal)
During geomagnetic storms, which are the primary periods for heavy ions from the solar wind to enter Earth’s magnetospheric space, the charge state of solar wind heavy ions during these storms has significant implications for studying the distribution and effects of heavy ions in the magnetosphere. We analyzed the states and variations of heavy ions during 158 interplanetary coronal mass ejection (ICME)–driven geomagnetic storm events using data from the Advanced Composition Explorer satellite and examined four of these events in detail. We found that the increase in the average charge state of heavy ions such as O, Mg, Si, and Fe is positively correlated with the intensity of the geomagnetic storm. Regarding the abundance ratio of heavy ions such as Ne, Mg, Si, and Fe relative to oxygen ions, the rate and magnitude of increase in abundance ratios during extreme geomagnetic storms ( Kp = 9) triggered by ICME events are significantly higher than those during other levels of geomagnetic storms. Additionally, we observed that although the average charge states of heavy ions such as O and Fe are correlated with the geomagnetic storm intensity induced by ICMEs, there are significant individual differences in the charge state variations of heavy ions.